How to read the Bible in changing times : understanding and applying God's word today - Strauss, Mark L., 1959- (Grand Rapids, Mich. : Baker Books, 2011)
"How do we read God's unchanging Word in a world that is always changing?How can words written thousands of years ago in different times and cultures apply to us today? Why do Christians obey certain commands in the Bible and ignore others? Some say commands to greet one another with a kiss or not to eat pork are merely 'cultural' but then insist that commands related to divorce, homosexuality, or the roles of women and men apply for all time. Are we just picking and choosing what we want to obey and what we want to ignore? Or are there consistent principles for interpreting and applying the Bible? How to Read the Bible in Changing Times shows you how to interpret and apply the Scriptures regardless of time and culture. It develops a heart-of-God approach that provides guidelines todetermine the meaning of the text in its original context analyze cultural features discern what the Bible teaches about God, his will, and his purposes apply the truths discovered to contemporary life situations. If you have ever struggled to see the connection between this ancient document and your world today, you will treasure this insightful book"--Publisher description.
Introduction : the unchanging word in a changing world -- What the Bible is not -- What the Bible is -- A heart-of-God hermeneutic : walking with God in his story -- Seeking the heart of God in dialogue : tradition, community, and the Spirit -- Finding the heart of God in the diverse genres of the Old Testament -- Finding the heart of God in the diverse genres of the New Testament -- When cultures collide : discerning the heart of God in cultural context.
Includes bibliographical references (pages 253-263) and index.
Keywords: Bible -- Hermeneutics